2017
DOI: 10.1186/s12871-016-0293-z
|View full text |Cite
|
Sign up to set email alerts
|

Effect of ultrasonography and fluoroscopic guidance on the incidence of complications of cannulation in extracorporeal cardiopulmonary resuscitation in out-of-hospital cardiac arrest: a retrospective observational study

Abstract: BackgroundIt remains unclear which cannulation method is best in cases of extracorporeal cardiopulmonary resuscitation (ECPR) for out-of-hospital cardiac arrest. We assessed the effect of ultrasound- and fluoroscopy-guided percutaneous cannulation on complication incidence, compared with that using only ultrasound guidance.MethodsThis single-center retrospective observational study was conducted between February 2011 and December 2015. In the comparison group, cannulation was performed percutaneously using onl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
30
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(32 citation statements)
references
References 33 publications
1
30
0
1
Order By: Relevance
“…Imaging modalities, including ultrasound and fluoroscopy can reduce vascular complications. 20 Therefore, we should actively utilize imaging modalities to reduce bleeding events for ECMO cannulation. In our study, there were no differences in baseline characteristics, ECMO complications, and transfusion between survivors and non-survivors in the stage 2 group.…”
Section: Discussionmentioning
confidence: 99%
“…Imaging modalities, including ultrasound and fluoroscopy can reduce vascular complications. 20 Therefore, we should actively utilize imaging modalities to reduce bleeding events for ECMO cannulation. In our study, there were no differences in baseline characteristics, ECMO complications, and transfusion between survivors and non-survivors in the stage 2 group.…”
Section: Discussionmentioning
confidence: 99%
“…Further, a retrospective study demonstrated that a hybrid ER significantly reduced the incidence of complications of cannulation of ECMO. 15 Thus, we could initiate ECMO within 18 min of arrival in the hybrid ER without any complication which prevented him from going into a cardiopulmonary Patient's perspective I remember that I was very surprised to hear that I was about to die. I do not really remember the days I spent in Saiseikai Yokohamashi Tobu Hospital.…”
Section: Discussionmentioning
confidence: 99%
“…Further, a retrospective study demonstrated that a hybrid ER significantly reduced the incidence of complications of cannulation of ECMO. 15 Thus, we could initiate ECMO within 18 min of arrival in the hybrid ER without any complication which prevented him from going into a cardiopulmonary arrest. Meanwhile, there are several issues such as the implementation cost, complexity and indication.…”
Section: Discussionmentioning
confidence: 99%
“…11 Similarly, one series found there was a statistically significant decrease in complication rate when US or fluoroscopy was used to place ECMO cannulas without delaying ECMO circuit start time. 12…”
Section: Ecmo Cannula Placement Positioning With Usmentioning
confidence: 99%